The gut microbiome is required for full protection against acute arsenic toxicity in mouse models. Issue 1 (December 2018) - Coryell, Michael; McAlpine, Mark; Pinkham, Nicholas; McDermott, Timothy; Walk, Seth
Abstract Arsenic poisons an estimated 200 million people worldwide through contaminated food and drinking water. Confusingly, the gut microbiome has been suggested to both mitigate and exacerbate arsenic toxicity. Here, we show that the microbiome protects mice from arsenic-induced mortality. Both antibiotic-treated and germ-free mice excrete less arsenic in stool and accumulate more arsenic in organs compared to control mice. Mice lacking the primary arsenic detoxification enzyme (As3mt) are hypersensitive to arsenic after antibiotic treatment or when derived germ-free, compared to wild-type and/or conventional counterparts. Human microbiome (stool) transplants protect germ-free As3mt-KO mice from arsenic-induced mortality, but protection depends on microbiome stability and the presence of specific bacteria, includingFaecalibacterium . Our results demonstrate that both a functional As3mt and specific microbiome members are required for protection against acute arsenic toxicity in mouse models. We anticipate that the gut microbiome will become an important explanatory factor of disease (arsenicosis) penetrance in humans, and a novel target for prevention and treatment strategies. It is unclear whether the gut microbiome can mitigate or exacerbate arsenic toxicity. Here, Coryellet al . show that the human gut microbiome protects mice from arsenic-induced mortality, with protection levels correlating with the relative abundance of the human commensalFaecalibacterium .